Chapter Dalla progettazione alla fruizione di un video a 360° - Luzzi, Damiana (Studi e saggi, 2022)
The chapter focuses on the design of a 360° video, paying attention also to accessibility issues. After having justified the decision to adopt the ADDIE model to manage the design process, it illustrates the five phases of the model, showing the workflow going from the design to the use of the 360° video, illustrating the template for the analysis of the didactic context and the various storyboards that are functional to the design.